High-performance thin-layer chromatography based concurrent estimation of biomarkers ent-phyllanthidine and rutin in the dried aerial parts of Flueggea virosa - Nasir A. Siddiqui; Ramzi A. Mothana; Adnan J. Al-Rehaily; Perwez Alam; Muhammad Yousaf; Sarfaraz Ahmed; Abdulrahman Alatar (Saudi Pharmaceutical Journal, 2017)
The biomarkers are needed to be defined for standardization purposes so that safe and effective herbal formulations can be catered to the society. There is an urgent need for statistical support of herbal drugs because most of the herbal products are still used in the non-standardized form. This study is based on the development of a simple and sensitive RP-HPTLC method for concurrent estimation of two biomarkers ent-phyllanthidine and rutin in the methanol extract of aerial parts of Flueggea virosa. The developed method was found to be simple, economic and sensitive. Separation and quantification were performed with acetonitrile: water (4:6 V/V) used as the mobile phase on glass-backed RP-HPTLC plate. Detection of absorption maxima and quantification was done at 310 nm of UV region. The developed chromatographic system was found to give a sharp band for ent-phyllanthidine and rutin at Rf 0.73 ± 0.01 and 0.68 ± 0.01, respectively. The linearity ranges for ent-phyllanthidine, and rutin were found to be 200–1600 ngband−1 and 100–1400 ngband−1, respectively, with correlation coefficients (r2 values) of 0.998 and 0.997, respectively. The percentage of ent-phyllanthidine and rutin was found to be 9.121 ± 0.02% and 1.018 ± 0.04% (w/w), respectively. The resolution of bands and separation of constituents in FVME exhibited the perfect optimization of the developed method. The validation statistics supports the proposed method for standardizing crude drugs as well as formulations of a natural product containing ent-phyllanthidine and rutin.